A perspectiva inclusiva no ensino de língua portuguesa como L2 para discentes surdos - Silva, Maria Zilda Medeiros da (2022)
The present research aims to present a linguistic study directed to the teaching and learning processes of the deaf person. Thus, we present a study with Portuguese language teachers, who work in an inclusive perspective, with the teaching of L2 to the deaf student. From the investigations, it was possible to know what are the difficulties of teachers to teach the teaching of Portuguese Language as L2, and what is the relationship with the communication of Libras with deaf students in classrooms of regular education in an inclusive way. In view of this information, we aim to present the importance of continuing education for the teaching of L2 to the deaf with the support of the visual resource, as well as Libras as L2 for the listener. The methodological course of the research is anchored in a case study with teachers of Portuguese as L2 in a state school, whose analysis criterion was through a semi-structured questionnaire with content analysis technique and quantitative-qualitative approach. As a general objective, we aim to develop, from the analysis of the questionnaire, a manual of guidelines for the teaching of L2 in an inclusive way and as a specific objective: To know what training teachers have to teach deaf students in the teaching classroom in an inclusive way ; Point out the methodological strategies and the main tools used to develop the Portuguese language as L2 for the deaf student; Knowing the difficulties found; Know the interest of teachers in training for L2. This research is intertwined with the professional experience of the author, a teacher who teaches in the multifunctional resource room with the Specialized Educational Services - AEE, in Libras as well as Portuguese Language as L2 for the deaf student. The experience of teaching in AEE to deaf students crossed the edges of the classroom and materialized in this study, in which we aimed support from some theorists, such as: Antunes (2003), Alves (2020), Bakhtin (2002), Quadros (2019) ), Skliar (2016), Perlin (2010) and Silva (2018). Therefore, with theoretical support together with the data analysis, it made it possible to develop as an intervention an orientation manual for Portuguese classes in an inclusive way for the deaf student.